Psychomotor Seizure Screening and in vitro Neuroprotection Assay of Hydrazones Derived from 2-Acetyl Thiophene - Mathew, Bijo; E. Mathew, Githa; Suresh, Jerad; Jaseel, Mohammed; Usman, D.; Subramanyan, P. N. Shiva; F. Safna, Kallivalappil; K. Vilapurathu, Jobin (Central Nervous System Agents in Medicinal Chemistry, 2017)
Background: Hydrazone core is a versatile structural linker for the development of various classes of antiepileptic agents. The aim of this study was to investigate the anticonvulsant activity of thiophene based hydrazones according to the antiepileptic drug development program protocol. Methods: The maximal electroshock-induced seizure and 6 Hz
Keywords: Anticonvulsant activity